O diálogo com o cético moral na fundamentação da ética discursiva de Jürgen Habermas - Frare, Jian Carlos (2017)
The present work has for objective to discourse on the dialogue established between the philosopher Jürgen Habermas and the moral skeptic argument during the recital of the Ethics of the Speech. Habermas, together with Karl-Otto Apel, develops an established moral theory “after-kantiana” under the reconstruction of universal presuppositions undeniable for any interaction. Such a proposal leaves from contents found already in the everyday of the individuals, these contents that are taken to a practical Discourse searched for the agreement of all in universal sense. For of being developed like a moral cognitivist, deontological, formalistic and universalist, the theory of the discursive ethics faces criticism as that of the impossibility of foundation moral norms valid. However, Habermas develops a theory that is based on a moral point of view, which guarantees the impartiality of the judgement of moral norms and, at the same time, it secures the universality through the principle of Universalization. This construction looks to surpass the abstraction of the historicity, characteristic of the proceduralist ethics, considering the consequences of his application still in the foundation.